Dynamics and Development of MSMEs Halal Products in the Covid-19 Pandemic: A Case Study in the Tourism Area of Pacitan Regency - Aminudin Ma'ruf; Nurdana Malik Fajar; Irfan Ramis (Fakultas Ekonomi Universitas Andalas, 2023)
MSMEs play a pivotal role in the community and sustainability of the Indonesian economy. This study explores and analyzes the developments and survival strategies of MSME actors in the Pacitan Regency. This study employs a qualitative method by taking data from interviews with 15 MSME actors in the Pacitan Regency. Due to the COVID-19 pandemic, MSME players in Pacitan Regency have experienced decreased sales and a lack of capital. The responses of MSME players in Pacitan Regency are decreasing sales turnover and increasing selling prices. One of the strategies MSME players in Pacitan Regency carry out to deal with COVID-19 is to sell online, reduce trade stock, make selling promos, and collaborate with other MSMEs. It is hoped that with this research, the government can pay attention to the good input these MSME actors give. In addition, MSME players are expected to be consistent with the strategy carried out by following government policies to continue to comply with health protocols in selling.